A review of Adelphocoris-Creontiades-Megacoelum complex (Hemiptera: Heteroptera: Miridae: Mirini), with descriptions of two new genera and four new species - Chérot, F.; Malipatil, M.b. (Zootaxa, 2016)
The Adelphocoris-Creontiades-Megacoelum complex of genera is reviewed. Diagnostic characters for each included genus and species are provided. Two new genera, Poppiomegacoelum n. gen. and Pseudomegacoelum n. gen., are proposed to accommodate Poppiomegacoelum gearyi n. sp. from Australia and four species from west Palearctic previously classified under Megacoelum Fieber, 1858 respectively. Three new species from Australia, Papua New Guinea and Solomon Islands are described: Adelphocorisella rubricornis n. sp., Waucoris solomonensis n. sp. and Waucoris tricolor n. sp. The following new combinations are made: Adelphocorisella brunnescens (Poppius, 1915) [for Adelphocoris brunnescens Poppius, 1915], A. relatum (Distant, 1904) [for Megacoelum relatum Distant, 1904], Macrolygus rubrus (Carvalho, 1987) [for Waucoris rubrus Carvalho, 1987], Miyamotoa mussooriensis (Distant, 1909) [for Megacoelum mussooriense Distant, 1909], Orientomiris ater (Poppius, 1915) [for Creontiades ater Poppius, 1915], O. brunneus (Poppius, 1914) [for Creontiades brunneus Poppius, 1914], O. furhstorferi (Poppius, 1915) [for C. furhstorferi Poppius, 1915], O. maculicollis (Poppius, 1915) [for C. maculicollis Poppius, 1915], O. marginatus (Poppius, 1915) [for C. marginatus Poppius, 1915], O. montanus (Poppius, 1915) [for C. montanus Poppius, 1915], O. monticola (Poppius, 1914) [for Megacoelum monticola Poppius, 1914], O. orientalis (Poppius, 1915) [for Creontiades orientalis Poppius, 1915], O. pallidicornis (Poppius, 1915) [for Megacoelum pallidicorne Poppius, 1915], O. ravana (Kirkaldy, 1909) [for Kangra ravana Kirkaldy, 1909], O. sumatranus (Poppius, 1915) [for Adelphocoris sumatranus Poppius, 1915], O. uzeli (Poppius, 1910) [for Creontiades uzeli Poppius, 1910), Poppiocapsidea tagalica (Poppius, 1915) [for Megacoelum tagalicum Poppius, 1915], Pseudomegacoelum angustum (Wagner, 1965) [for Megacoelum angustum Wagner, 1965], P. beckeri (Fieber, 1870) [for M. beckeri (Fieber, 1870)], P. irbilanum (Linnavuori, 1988) [for M. irbilanum Linnavuori, 1988], P. quercicola (Linnavuori, 1965) [for M. quercicola Linnavuori, 1965], Waucoris poppiusi Chérot & Malipatil [new name and new combination for Megacoelum papuanum Poppius, 1915]. The following new synonymies are established: Creontiades vittipennis Reuter, 1905 (valid name) = Creontiades vitticollis Poppius, 1915 (new subjective synonym), Poppiocapsidea biseratensis (Distant, 1903) (valid name) = Megacoelum townsvillensis Distant, 1904 (new subjective synonym). Cheilocapsidea insignis (Distant, 1909) is recorded from Laos and the male genitalic structures are briefly described for the first time. A lectotype is designated for Capsus antennatus Kirby, 1891, Creontiades ater Poppius, 1915, Creontiades brunneus Poppius, 1914, Creontiades fruhstorferi Poppius, 1915, Creontiades marginatus Poppius, 1915, Creontiades uzeli Poppius, 1910, Megacoelum mussooriensis Distant, 1909, Megacoelum relatum Distant, 1904, and Megacoelum townsvillensis Distant, 1904 (original combinations). A key for the genera included in the Adelphocoris-Creontiades-Megacoelum complex is given.